2022
DOI: 10.1177/00178969221128641
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical models: Can they make a difference to girls’ in-class physical activity?

Abstract: Background: Research has shown the positive connections between physical activity and health, and physical education has been shown to influence the motivation to participate in physical activities. Student-centred pedagogical models encouraging active learning may be capable of bringing about changes in girls’ physical activity. Objective: The aim of the study was to investigate whether a hybrid pedagogical model could make a difference to adolescent girls’ in-class physical activity levels. Design, setting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It seems that enjoyment in PE classes could be affected by other factors regardless of the model applied. Factors such as class content, motivational climate or the teacher's attitude, among others, could be considered [23,92]. Regarding enjoyment, despite there being no initial differences between the groups, both for boys and girls, the improvements in the values did not provide significant differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It seems that enjoyment in PE classes could be affected by other factors regardless of the model applied. Factors such as class content, motivational climate or the teacher's attitude, among others, could be considered [23,92]. Regarding enjoyment, despite there being no initial differences between the groups, both for boys and girls, the improvements in the values did not provide significant differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Memmert and Harvey [23] suggested that GP indices should be prioritized for age groups in which the reflective parts of the session can have a strong impact, but that it should always be compared with GI. Only one prior study on hybrid SE/TGfU has considered this issue [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations